2014
DOI: 10.1037/fam0000035
|View full text |Cite
|
Sign up to set email alerts
|

Income and children’s behavioral functioning: A sequential mediation analysis.

Abstract: Children from low-income households tend to exhibit higher levels of conduct problems and emotional problems, yet the pathways linking economic disadvantage to children's behavioral functioning are not well understood. This study uses data from the Early Steps Multisite (ESM) project (N = 731) to investigate associations between family income in early childhood and children's conduct problems and emotional problems in middle childhood. The study explores whether the associations from income to child conduct pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 62 publications
5
31
1
2
Order By: Relevance
“…In an example of this type of analysis, Connell and colleagues (2008) found that the Family Check-Up was more successful in reducing problem behavior from ages 2 to 4 among children with CP and co-occurring internalizing problems than children with CP alone. This finding is somewhat surprising finding based on the relative brevity of the Family Check-Up (i.e., mean of 3–4 sessions per year over two years), but consistent with other intervention research suggesting that initial levels of problem behavior predict more positive intervention outcomes (Conduct Problems Prevention Research Group, 2007, 2011; Shelley & Shaw, 2012). …”
Section: Future Directions For Research On the Development Of Early Csupporting
confidence: 86%
See 2 more Smart Citations
“…In an example of this type of analysis, Connell and colleagues (2008) found that the Family Check-Up was more successful in reducing problem behavior from ages 2 to 4 among children with CP and co-occurring internalizing problems than children with CP alone. This finding is somewhat surprising finding based on the relative brevity of the Family Check-Up (i.e., mean of 3–4 sessions per year over two years), but consistent with other intervention research suggesting that initial levels of problem behavior predict more positive intervention outcomes (Conduct Problems Prevention Research Group, 2007, 2011; Shelley & Shaw, 2012). …”
Section: Future Directions For Research On the Development Of Early Csupporting
confidence: 86%
“…There has been much value in adopting family stress models, first articulated by Elder (1974), and later refined by others (Conger et al, 1992; McLoyd, 1990), in which the stressors associated with poverty on emerging child CP are conceived to be mediated by effects on parenting. However, more recent efforts in characterizing the daily environmental stressors experienced by low-income children also have noted their greater exposure to structural deficits in the quality of their housing (e.g., leaky roofs, rodent infestation, poor heating), higher levels of air pollution, neighborhood levels of crime including shootings, and higher levels of parental psychopathology and family conflict/chaos in the home (Evans, 2001, 2004; Evans, Gonnella, Marcynyszyn, Gentile, & Salpekar, 2005; Shelleby et al, 2012). Models of CP have traditionally found that associations between socioeconomic risk and child CP are mediated by parenting attributes (Conger et al, 1992; Patterson, 1982), a pathway that would be even more readily evident during early versus later childhood based on young children’s greater psychological and physical dependence on parents during early childhood.…”
Section: Future Directions For Research On the Development Of Early Cmentioning
confidence: 99%
See 1 more Smart Citation
“…This impact was most strongly felt by caregivers in the lowest income quintile (Williams, Murray, McCrory, & McNally, 2013). The additional stress put on families due to increased economic hardships may have influenced the relationship between our measure of stress at wave 1 and functioning at wave 2 (Fahey & Nixon, 2014; Shelleby et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…, mental and physical health; marital stability) is part of the family and ecological context of the child, which shapes quality of parental investment and, through it, child developmental outcomes such as emerging life history strategies. Longitudinal analyses found that maternal depression in early childhood (predicted by lower socioeconomic status and greater household unpredictability in terms of parental and residential changes) was associated with increased household chaos, more parental hassles, harsher parenting at ages 4–5 years old, and earlier onset of sexual activity [12,17]. Moreover, other research has shown that exposure to unpredictable conditions in early childhood can impact an individual’s approach toward parenting, decreasing supportive parenting mostly in men [18 •• ].…”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 99%